ANALISIS PENGARUH KUALITAS PELAYANAN, CITRA PERUSAHAAN, DAN KEPUASAN, TERHADAP LOYALITAS (STUDI KASUS PADA PT. MNC SEKURITAS PANGKALPINANG - Sella, Alvonsus Niko; Zamhari; Panjaitan, Fery (Jurnal Ilmiah Niaga Bisnis Elektronik, 2023)
The method used in this research is a descriptive method with a quantitative approach to find the relationship between the independent variables (service quality, corporate image, and satisfaction) with the dependent variable (loyalty) using statistical formulas. While the statistical formula used to test the hypothesis is multiple linear regression analysis, the sample in this study amounted to 67 people. The test results for the service quality variable (X1) where tcount (4.486) > ttable (1.669) mean that the service quality variable (X1) has a partial effect on loyalty (Y). The test results for the company image variable (X2) where tcount (-0.221) < ttable (1.669) mean that the corporate image variable (X2) has no partial effect on loyalty (Y). The test results for the satisfaction variable (X3) where tcount (7.121) > ttable (1.669) mean that the price variable (X3) has a partial effect on loyalty (Y).